NKT Cells in Neurological Diseases - Cui, Yu; Wan, Qi (Frontiers in Cellular Neuroscience, 2019)
Natural killer T (NKT) cells are a unique subset of T lymphocytes with the expression of T cell receptor (TCR) and NK cell lineage receptors. These cells can rapidly release large quantities of cytokines and function as a bridge between innate and adaptive immunity. To date, multiple reports have investigated the role of NKT cells under various pathological conditions, such as cancer, autoimmune disease, and infection. Knowledge about NKT cells in neurological diseases is increasing, albeit limited. Here, we review evidence for the involvement of NKT cells in neurological diseases, and discuss immunotherapeutic potential and future study goals. As the development and function of NKT cells become increasingly well understood, the next few years should yield many new insights into NKT cell function, and mechanistic regulation in neurological disorders.